Credit Booms and Macroeconomic Dynamics : Stylized Facts and Lessons for Low-Income Countries - Arena, Marco; Bouza, Serpil; Dabla-Norris, Era.; Gerling, Kerstin (Washington, D.C. : International Monetary Fund, 2015)
Using a comprehensive database on bank credit, covering 135 developing countries over the period 1960-2011, we identify, document, and compare the macro-economic dynamics of credit booms across low- and middle-income countries. The results suggest that while the duration and magnitude of credit booms is similar across country groups, macro-economic dynamics differ somewhat in low-income countries. We further find that surges in capital inflows are associated with credit booms. Moreover, credit booms associated with banking crises exhibit distinct macroeconomic dynamics, while also reflecting a potentially large deviation of credit from country fundamentals. These results suggest that low-income countries should remain mindful of the inter-linkages between financial liberalization, increased cross-border banking activities, and rapid credit growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet